PENGARUH KOMBINASI JARAK TANAM DAN PUPUK FOSFAT TERHADAP PERTUMBUHAN, KOMPONEN HASIL DAN HASIL TANAMAN WIJEN (Sesamum indicum L.) VARIETAS SUMBERREJO-1(Sbr-1) - Nugroho Wahyu Widodo; Achmad Faqih (Agroswagati Jurnal Agronomi, 2022)
The results of this experiment can be seen the effect of the combination of spacing and phosphate fertilizer on the growth and yield of sesame (Sesamun Indicum L), Varieties Sumberrejo-1. The experiment was carried out in Mekarjaya Gantar Village, Indramayu - West Java, in July - November 2021. The experimental method was Randomized Block Design (RAK) with a combination pattern, with two treatments repeated three times, namely the combination treatment of phosphate fertilizer application (100 kg/ha, 150 kg/ha, 200 kg/ha) with spacing treatments (25 cm x 50 cm, 25 cm x 60 cm, and 25 cm x 70 cm). The experimental data were processed using linear model statistical tests, analysis of variance, and Scott-knot cluster further test analysis. The correlation between treatment with growth components and sesame yield was used Product Moment correlation coefficient. The experimental results showed: (1) The combined treatment of distance and phosphate showed plant height at 14 HST, leaf number at 14 HST, and seed weight per clump, but did not affect plant height at 28 HST and 42 HST, leaf number at 28 HST. and 42 HST, stem diameter, root compaction, leaf area index, plant growth rate, fruit number per clump, fruit number per plot, fruit weight per cluster, fruit weight per plot, 1000 seeds, and seed weight per plot ( 2) The highest seed weight of each plot was produced by a combination of treatments F, which was 25 x 60 cm and phosphate 200kg/ha with an average weight of 1.03 kg (together with 1,715 tan/ha), (3) There was a significant correlation between plant height and leaf number at 28 HST and 42 HST with seed weight of each plot in the strong category. However, there was no significant correlation between plant height and leaf number at 14 HST with seed weight in each plot with weak and simple categories.